The impact of alcohol taxation changes on unrecorded alcohol consumption: A review and recommendations - Rehm J. (2023)
Background: The diverse forms of unrecorded alcohol, defined as beverage alcohol not registered in official statistics in the country where it is consumed, comprise about one fourth of all alcohol consumed worldwide. Since unrecorded alcohol is usually cheaper than registered commercial alcohol, a standard argument against raising alcohol excise taxes has been that doing so could potentially result in an increase in unrecorded consumption. This contribution examines whether increases in taxation have in fact led to increases in consumption of unrecorded alcohol, and whether these increases in unrecorded alcohol should be considered to be a barrier to raising taxes. A second aim is to outline mitigation strategies to reduce unrecorded alcohol use. Methods: Narrative review of primary and secondary research, namely case studies and narrative and systematic reviews on unrecorded alcohol use worldwide. Results: Unrecorded alcohol consumption did not automatically increase with increases in taxation and subsequent price increases of registered commercial alcohol. Instead, the level of unrecorded consumption depended on: a) the availability and type of unrecorded alcohol; b) whether such consumption was non-stigmatized; c) the primary population groups which consumed unrecorded alcohol before the policy change; and d) the policy measures taken. Mitigation strategies are outlined. Conclusions: Potential increases in the level of unrecorded alcohol consumption should be considered in the planning and implementation of substantial increases in alcohol taxation. However, unrecorded consumption should not be considered to be a principal barrier to implementing tax interventions, as evidence does not indicate an increase in consumption if mitigation measures are put in place by governments.